Le pont-tunnel Louis-Hippolyte-La Fontaine : aux origines d'une infrastructure routière régionale - Gaudry, William (Université du Québec à Montréal, 2022)
Keywords: Autoroutes; Ponts; Tunnels

Les obstacles à l'actualisation des banlieues d'après-guerre dans la région métropolitaine de Montréal. Le cas de Laval-des-Rapides et Pont-Viau - Descôteaux Fréchette, Samuel (INRS et UQAM, 2016)
Keywords: Banlieue; Laval; Laval-des-Rapides; Pont-Viau

Building landscape narratives: the material and visual culture of bridge construction in Montreal, 1854-1930 - Braiden, Heather (Université McGill, 2021)
Keywords: Ponts; Victoria (pont)

“Far From Uninteresting”: Getting to Know the St. Lawrence River at Montreal During the Construction of the Victoria Bridge - Braiden, Heather (Urban History Review/Revue d'histoire urbaine, 2022)
In northern cities like Montreal, Quebec, Canada, the winters are long, and the construction season is condensed. In the mid-nineteenth century, knowing the St. Lawrence River’s seasonal variations and local construction customs helped railway and bridge builders save time and frustration during the very short working seasons. In this article, I investigate how technical and quasi-technical communications generated during the construction of the Victoria Bridge (1854–1860) are a rich source of urban knowledge. By examining visual and textual evidence in The Construction of the Great Victoria Bridge in Canada, I demonstrate how representations of the construction process are a tangible medium through which practical experience and a personal way of knowing the urban landscape are mediated. I argue that everyday experience and tacit knowledge move between social worlds and inform how audiences know and understand the colonial city.
Keywords: Victoria (pont)

Retrouver les lieux de passages - Lebleu, Jacques (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2024)
Keywords: Ponts; Rivière des Prairies; Sault-au-Récollet

Une île sans partage: la domination de Montréal à l'ère d'une nouvelle dynamique insulaire - Fougères, Dany; Shaffer, Valérie (Histoire de Montréal et de sa région, 2012)
Keywords: Automobile; Banlieue; Centre-ville; Hôtel de ville; Maires; Ponts; Quartiers; Routes; Réformistes; Tramways; Vieux-Montréal

An Undivided Island: Domination at the Dawn of a New Era - Fougères, Dany; Shaffer, Valérie (Montreal: The History of A North American City, 2018)
Keywords: Automobile; Banlieue; Centre-ville; Hôtel de ville; Maires; Ponts; Quartiers; Routes; Réformistes; Tramways; Vieux-Montréal

On a marché sur le boulevard des Galeries d’Anjou (Montréal): bref retour d’enquête sur une artère de banlieue en voie d’intensification - Kiti, Mesmin; Sénécal, Gilles; Hamel, Pierre J. (Sites publics, lieux communs (2): urbanité et aménagement des rues et des ponts au Canada et au Québec, 2008)
Keywords: Anjou; Arrondissements; Banlieue; Rues